البنك المركزي وتنظيم المعاملات المصرفية الالكترونية - يلالي, بوبكر; العبسي, علي (جامعة الوادي - University of Eloued, 2018)
تمثل المعاملات المصرفية الالكترونية احد أهم الابتكارات التي افرزها التقدم التكنولوجي، حيث تثير وسائلها ومعاملاتها بمختلف صورها وأشكالها عددا من المسائل الاقتصادية والنقدية والتي يتعين الاهتمام بها خاصة في ظل المتغيرات الحديثة التي تعمل في ظلها السياسة النقدية وتؤثر على فعاليتها، وتأتي هذه المتغيرات في إطار ما يسمى بالتحرير المالي وذلك في ظل الحرية غير المحدودة لرؤوس الأموال. وخلصت الدراسة الى دور الكبير الذي يلعبه البنك المركزي في التقليل من شأن التحديات والمشكلات التي قد تنشأ في مجال المعاملات المصرفي الالكترونية، وذلك من خلال مراجعة تشكيل سياسته النقدية استجابة لتلك التطورات التكنولوجية، وبناء عليه يتم تطوير الإطار التنظيمي للسياسة النقدية للبنك المركزي وفقا لتلك التطورات لضمان عدم تهديد تلك التطورات للسياسة النقدية للبنك المركزي The electronic means of payment represent one of the most important innovations that have been produced by technological progress. The means of payment in various forms and forms raise a number of economic and monetary issues which need to be taken care of, especially in light of the recent changes under which monetary policy operates and affect its effectiveness. With financial freedom, in the unlimited freedom of capital. The study concluded the role played by the Central Bank in minimizing the challenges and problems that may arise in the creation of electronic money by reviewing the formation of its monetary policy in response to these technological developments. Accordingly, the regulatory framework of the monetary policy of the Central Bank is developed according to these developments to ensure that Threatening those developments to the monetary policy of the central bank.
The Central Bank and the regulation of electronic banking transactions
مقال
Keywords: وسائل الدفع الإلكترونية، النقود الإلكترونية، الخدمات المالية، السياسة النقدية، المصارف المركزية; Electronic payment methods, electronic money, financial services, monetary policy, central banks